measuring of usability billboard lease system Sys-BL - Wahyu Joni Kurniawan; Rometdo Muzawi (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2021)
Billboards or commonly called billboards, are one of the most commonly used advertising methods, this is because their position in public spaces is also traversed by road users. The billboard rental system is a system built to make it easier for consumers to see and choose the position of the desired billboard location according to availability, as well as to provide billboard rental services to consumers who will use it. However, every system that is built must have a measurement of its usefulness in terms of effectiveness and efficiency as well as the level of user satisfaction when this system is used. To find out how useful the system is, the usability test measurement is used. Usability is a measure of user experience in using a system based on the criteria of learnability, efficiency, memorability, errors and satisfaction which is formed into 19 questionnaire questions with a value range for each question is 1 to 5.Where the respondents consist of 20 respondents, both business actors and individuals. . The results of the recapitulation of the questionnaire obtained an average rating for each criterion in order of 3.54, 4.03, 4.05, 1.8, and 3.46. This proves that the gis web-based billboard rental system has a good level of usability for system users.